Compassionate access anti‐tumour necrosis factor‐α therapy for ulcerative colitis in Australia: the benefits to patients. Issue 6 (June 2015) - Costello, S. P.; Ghaly, S.; Beswick, L.; Pudipeddi, A.; Agarwal, A.; Sechi, A.; O'Connor, S.; Connor, S. J.; Sparrow, M. P.; Bampton, P.; Walsh, A. J.; Andrews, J. M.; et al.
Abstract Background The efficacy of infliximab has been demonstrated in patients with both acute severe and moderate‐severe ulcerative colitis (UC). However, there is a need for 'real‐life data' to ensure that conclusions from trial settings are applicable in usual care. We therefore examined the national experience of anti‐tumour necrosis factor‐α (TNF‐α) therapy in UC. Methods Case notes review of patients with UC who had received compassionate access (CA) anti‐TNF‐α therapy from prospectively maintained inflammatory bowel disease databases of six Australian adult teaching hospitals. Results Patients either received drug for acute severe UC (ASUC) failing steroids (n = 29) or for medically refractory UC (MRUC) (n = 35). In ASUC, the treating physicians judged that anti‐TNF‐α therapy was successful in 20/29 patients (69%); in these cases, anti‐TNF‐α was able to be discontinued (after 1–3 infusions in 19/20 responders) as clinical remission was achieved. Consistent with this perceived benefit, only 7/29 (24%) subsequently underwent colectomy during a median follow up of 12 months (interquartile range (IQR) 5–16). Eight of the 35 patients with MRUC (23%) required colectomy during a median follow up of 28 months (IQR 11–43). The majority of these patients (20/35 or 57%) had anti‐TNF‐α therapy for ≥4 months, whereas, 27/29 (93%) of ASUC patients had CA for ≤3 months. Conclusions These data show an excellent overall benefit for anti‐TNF‐α therapy in both ASUC and MRUC. In particular, only short‐duration anti‐TNF‐α was required in ASUC. These real‐life data thus support the clinical trial data and should lead to broader use of this therapy in UC.